THE ROLE OF CUSTOMER REVIEWS, INFLUENCER MARKETING, AND LIVE STREAMING FEATURES IN INFLUENCING PURCHASE DECISIONS ON THE SHOPEE PLATFORM IN MEDAN - Andy Wijaya; Purnama Yanti Purba; Andre; Nasib (ZILLZELL MEDIA PRIMA, 2026)
This study seeks to examine the impact of customer reviews, influencer marketing, and live streaming on purchasing decisions on the Shopee platform in Medan City. This research employs a quantitative methodology utilizing multiple linear regression analysis approaches. The research sample comprised 95 Shopee customers chosen through a purposive selection procedure. The results demonstrate that customer evaluations, influencer marketing, and live streaming exert a positive and significant impact on purchasing decisions, evidenced by a coefficient of determination of 0.856. This shows that these three things have a big effect on what people buy. The managerial implications of this study indicate that businesses should make the most of customer reviews to boost trust and happiness. To get more people interested in your brand and reach more people with your marketing, you should also make the most of influencer marketing. Live broadcasting can also make shopping more participatory and fun, which can help people make better selections about what to buy. Businesses may boost consumer loyalty and their competitiveness in the e-commerce sector, which is getting more and more competitive, by using these three things well.